Global leadership for social justice taking it from the field to practice - Boske, Christa; Diem, Sarah (Bingley, U.K. : Emerald, 2012)
Global leadership for social justice : taking it from the field to practice proposes perspectives for conceptualizing the preparation of leaders for social justice and equity-oriented work in schools. Although faculty in the field of education have prepared thousands of school leaders, and the research continues to expand, limited research exists regarding how to prepare leaders for social justice work in schools, especially considering international contexts. This book builds on extant empirical and theoretical work in the area of educational leadership, and deepens understanding of what leading for social justice and equity-oriented work looks like within diverse schools.
ch. 1. Mitigating the impact of educational policies in rural Kenya / Teresa Wasonga, Miriam Bageni Mwita -- ch. 2. Listening to student voice : toward a more inclusive theory for research and practice / Katherine Cumings Mansfield, Anjalé Welton, Mark Halx -- ch. 3. Re-thinking the preparation of educational leaders : utilizing q-methodology to facilitate the development of socially just leaders / Bradley W. Carpenter, Sarah Diem -- ch. 4. A program designed to reculture educational leadership / Carl Kalani Beyer -- ch. 5. Preparing school leaders for social justice : examining the efficacy of program preparation / Karie Huchting, Jill Bickett -- ch. 6. Racial identity development in principal preparation programs : linking theory to practice / Frank Hernandez -- ch. 7. Davis K-8 school : utilizing transformational leadership to drive inclusive practice / Thad Dugan -- ch. 8. Teacher leadership : leading for social justice in teacher education / Walter S. Gershon -- ch. 9. Standing still is no longer an option : understanding how to prepare school leaders to interrupt oppressive practices / Christa Boske -- ch. 10. A tale of two scholar-practitioners : transforming practices at their sites and beyond / Peg Winkelman, Michelle Collay -- ch. 11. Toward a framework for an inclusive model of social justice leadership preparation : equity-oriented leadership for students with disabilities / Barbara L. Pazey, Heather A. Cole, Shernaz B. Garcia -- The future of educational leadership preparation : creating the capacity for caring, equity, and leading for social justice / Christa Boske, Sarah Diem.
Includes index.
Print version record
Keywords: Education -- Administration -- General; Organization & management of education; Educational leadership; Social justice